Legacy of a Library Leader: Anne Harrison. Issue 4 (2nd October 2021) - Birkic, Vesna
ABSTRACT: Anne Harrison (1923–1992) was a pioneering academic medical librarian who worked at the Brownless Medical Library (BML), the University of Melbourne from 1949–1983. In the early years, there was unprecedented demand for postgraduate courses and a limited budget to build a collection in support of the research needs of the faculty. However, with foresight, Harrison contributed significantly to the development of the University's medical faculty, and also to the wider medical library fraternity in Australia. Those developments included moving the library from a wing of the University's original Pathology building into a newly established Brownless Medical Library in 1967 and a major shift from print indexes to the use of online databases, such as MEDLINE in 1977. She was also instrumental in the establishment and administration of the Central Medical Library Organisation, an important service through which Victorian medical libraries were able to access, by telephone, a location service for journals and books and to cooperate in a duplicate serials exchange program. This paper aims to increase the understanding of present-day health librarianship by revisiting the principles of library service established under the leadership of Miss Anne Harrison. This reflection is based on an interview and previous publications on the topic about Harrison and the period in medical librarianship.